Effect of vibro-milling time on phase transformation and particle size of zirconia nanopowders derived from dental zirconia-based pre-sinter block debris - Sriboonpeng C. (2017)
© 2017, Chiang Mai University. All rights reserved. Zirconia (ZrO 2 ) nanopowders (with smallest size 35 nm) derived from recycling of dental ZrO 2 -based pre-sinter block debris were prepared by using a rapid vibro-milling technique. The detailed investigations considering the roles of vibro-milling times on crystal structure, particle size distribution and morphological evolution of the obtained powders were investigated by using a combination of X-ray diffraction (XRD), laser diffraction, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) techniques. In general, it has been found that the monoclinic- and the tetragonal-ZrO 2 phases tend to form together. The increased milling time was found to play a significant role on broadening of particle size distribution together with fluctuation of ZrO 2 particle size. Moreover, SEM results showed that these ZrO 2 powders consist of a variety of agglomerated particle size, depending on their experienced vibro-milling times. In addition, TEM technique was also used to confirm the crystallographic phases of the ZrO 2 nanoparticle supporting the XRD results. These findings revealed that a narrower particle size distribution of these ZrO 2 nanopowders can be tailored by employing an appropriate choice of the milling time.